Temporal changes in global soil respiration since 1987 - Lei, Jiesi; Guo, Xue; Zeng, Yufei; Zhou, Jizhong; Gao, Qun; Yang, Yunfeng (Nature communications, 2021)
As the second-largest terrestrial carbon (C) flux, soil respiration ( R S ) has been stimulated by climate warming. However, the magnitude and dynamics of such stimulations of soil respiration are highly uncertain at the global scale, undermining our confidence in future climate projections. Here, we present an analysis of global R S observations from 1987–2016. R S increased ( P < 0.001) at a rate of 27.66 g C m −2 yr −2 (equivalent to 0.161 Pg C yr −2 ) in 1987–1999 globally but became unchanged in 2000–2016, which were related to complex temporal variations of temperature anomalies and soil C stocks. However, global heterotrophic respiration ( R h ) derived from microbial decomposition of soil C increased in 1987–2016 ( P < 0.001), suggesting accumulated soil C losses. Given the warmest years on records after 2015, our modeling analysis shows a possible resuscitation of global R S rise. This study of naturally occurring shifts in R S over recent decades has provided invaluable insights for designing more effective policies addressing future climate challenges. Soils hold massive amounts of carbon that hangs in the balance of microbial respiration and climate warming. Here the authors analyze a global dataset starting in 1987 and find through modeling that though soil respiration change had flatlined, recently it has resumed increasing owing to global warming.